2013
DOI: 10.1136/bjophthalmol-2012-302451
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of vascular endothelial growth factor before and after intravitreal injection of bevacizumab, ranibizumab and pegaptanib in patients with age-related macular degeneration, and in patients with diabetic macular oedema

Abstract: Bevacizumab significantly reduces the level of VEGF in the blood plasma for up to one month in patients with DME as well as in those with ARMD. No significant systemic effects of intravitreal ranibizumab or pegaptanib on plasma VEGF could be observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
97
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 32 publications
6
97
1
5
Order By: Relevance
“…In the present study, a similar off-target effect was observed in all patients treated with aflibercept. In both studies, no significant effects on plasma VEGF levels could be detected after intravitreal ranibizumab application (Zehetner et al 2013). The data of our current study for aflibercept are in line with the recent findings of Wang et al (2014) who describe significantly suppressed systemic VEGF levels 1 month after intravitreal aflibercept injection and no significant effects for ranibizumab.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In the present study, a similar off-target effect was observed in all patients treated with aflibercept. In both studies, no significant effects on plasma VEGF levels could be detected after intravitreal ranibizumab application (Zehetner et al 2013). The data of our current study for aflibercept are in line with the recent findings of Wang et al (2014) who describe significantly suppressed systemic VEGF levels 1 month after intravitreal aflibercept injection and no significant effects for ranibizumab.…”
Section: Discussionsupporting
confidence: 82%
“…Aflibercept, similar to bevacizumab induces a significant reduction of VEGF in the blood plasma persisting throughout the entire observational period of our study (Matsuyama et al 2010;Carneiro et al 2012;Zehetner et al 2013;Wang et al 2014). VEGF is a multifunctional cytokine that regulates biological functions in endothelial cells in adult vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by measuring serum rather than plasma VEGF, a significant portion of the VEGF measured would include VEGF released by platelets, which artificially increases systemic levels of VEGF measured and may mask subtle changes in VEGF levels. 7,18 Subsequent studies measuring plasma VEGF have also reported significant decreases in plasma VEGF following intravitreal bevacizumab, and non-statistically significant decreases in plasma VEGF following intravitreal ranibizumab, [5][6][7][8][9] which supports the IVAN findings, but remains at odds with data from the oncology literature.…”
Section: Introductioncontrasting
confidence: 47%
“…1 Different anti-VEGF agents also have different molecular structures, different transmissibility across the blood-retinal barrier, and different systemic half-lives, so could potentially have different effects on systemic VEGF levels. 1,[6][7][8][9] Ranibizumab is a recombinantly produced, humanized monoclonal antibody fragment (Fab) designed for intraocular use that binds and inhibits all biologically active isoforms of human VEGF. 10 Its transmissibility across the blood-retinal barrier is lower than that of fulllength molecules, but systemic bioavailability of ranibizumab has been reported post intravitreal injections.…”
Section: Introductionmentioning
confidence: 99%